Disjecta membra (PHILM. Rivista di filosofia e cinema, 2024)
In 1984, Morgan Fisher made the film Standard Gauge, a 16mm autobi- ography that explores the artist’s personal relationship with motion picture film, focusing on the 35mm format. Alternating between a historical and technical introduction and a subjective narrative, Fisher narrates his fascination with the “residues” of the film industry, such as film fragments and discarded materials. Shot with an artisanal, single-shot approach, the film reflects on the affective and cultural value of film objects, between autobiography, montage and aesthetic theory, making it a visual essay on film materials and memory.